Effects of Gabapentin on Pain and Opioid Consumption after Abdominal Hysterectomy - Fatemeh Frouzanfard; Mohammed Reza Fazel; Azadeh Abolhasani; Esmaeil Fakharian; Golmabas Mousavi; Alireza Moravveji (Pain Research and Management)
BACKGROUND: Postoperative pain is an important factor affecting anesthesia and surgery.